The limiting factors of land suitability for sandalwood (Santalum album) in Sumba Island, Indonesia: - HERY KURNIAWAN; DANI PAMUNGKAS (Society for Indonesian Biodiversity, 2020)
Abstract. Kurniawan H, Pamungkas D. 2020. The limiting factors of land suitability for sandalwood (Santalum album) in Sumba Island, Indonesia. Biodiversitas 21: 3364-3372. The land suitability assessment for sandalwood is very important for the successful cultivation and development of sandalwood (Santalum album Linn.) in Sumba Island, East Nusa Tenggara Province, Indonesia. The map of land suitability classification for sandalwood is currently available. The land suitability assessment is determined based on designated indicators and predictors. It is important to identify the most influential measures in a particular area to determine the suitable treatment to be applied to the sandalwood plant, as well as to recognize the land suitability evaluation swiftly and efficiently. This study was aimed to determine the variables of indicators or verifiers that have the strongest relationship with the land suitability class for sandalwood. Regression method was used to develop the relationship model and to determine the level of the relationship through the coefficient of determination. The result shows that P2O5 content was the most influential factor to determine the land suitability class for sandalwood in Sumba Island.